2021
DOI: 10.3390/cancers13163993
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-Responsive Elements Enriched with Alu Repeats May Contribute to Distinctive PPARγ–DNMT1 Interactions in the Genome

Abstract: Background: PPARγ (peroxisome proliferator-activated receptor gamma) is involved in the pathology of numerous diseases, including UM and other types of cancer. Emerging evidence suggests that an interaction between PPARγ and DNMTs (DNA methyltransferase) plays a role in cancer that is yet to be defined. Methods: The configuration of the repeating elements was performed with CAP3 and MAFFT, and the structural modelling was conducted with HDOCK. An evolutionary action scores algorithm was used to identify oncoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Recently, Pazienza et al demonstrated that PPARγ and DNMT1 are equally expressed in human pancreatic cancer cell lines, suggesting their importance in cancer genesis [ 42 ]. For their part, Ceccarelli et al proposed that the activation of PPARγ by eicosatetraenoic acid improves the interaction with DNMT1 and HDAC1 in the CpG islands of the Hic-1 gene [ 43 ], while Sharma A et al, examined the PPARγ-DNMT1 interaction through PPAR-binding elements (PPRE) in an in silico model [ 44 ]. Our molecular docking analyses suggest that PFD acts as an agonist ligand of PPARγ-LBD, facilitating the formation of complexes with the BAH1 domain of DNMT1 (ΔG −23.48 kcal/mol), enhancing its methyltransferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pazienza et al demonstrated that PPARγ and DNMT1 are equally expressed in human pancreatic cancer cell lines, suggesting their importance in cancer genesis [ 42 ]. For their part, Ceccarelli et al proposed that the activation of PPARγ by eicosatetraenoic acid improves the interaction with DNMT1 and HDAC1 in the CpG islands of the Hic-1 gene [ 43 ], while Sharma A et al, examined the PPARγ-DNMT1 interaction through PPAR-binding elements (PPRE) in an in silico model [ 44 ]. Our molecular docking analyses suggest that PFD acts as an agonist ligand of PPARγ-LBD, facilitating the formation of complexes with the BAH1 domain of DNMT1 (ΔG −23.48 kcal/mol), enhancing its methyltransferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Sharma A et al evaluated in an in-silico model the potential role of PPARγ-DNMT1 interaction via PPAR-binding elements (PPRE) [43]. This evidence indicates that is possible that PFD activates PPARγ facilitating the formation of complexes with BAH1 domain of DNMT1, thus increasing the activity of this enzyme.…”
Section: Discussionmentioning
confidence: 99%